Randomized clinical trial: effect of the 5‐HT4 receptor agonist revexepride on reflux parameters in patients with persistent reflux symptoms despite PPI treatment. Issue 2 (21st December 2014) - Tack, J.; Zerbib, F.; Blondeau, K.; des Varannes, S. B.; Piessevaux, H.; Borovicka, J.; Mion, F.; Fox, M.; Bredenoord, A. J.; Louis, H.; Dedrie, S.; Hoppenbrouwers, M.; et al.
Abstract Background Approximately, 20–30% of patients with gastro‐esophageal reflux disease (GERD) experience persistent symptoms despite treatment with proton pump inhibitors (PPIs). These patients may have underlying dysmotility; therefore, targeting gastric motor dysfunction in addition to acid inhibition may represent a new therapeutic avenue. The aim of this study was to assess the pharmacodynamic effect of the prokinetic agent revexepride (a 5‐HT4 receptor agonist) in patients with GERD who have persistent symptoms despite treatment with a PPI. Methods This was a phase II, exploratory, multicenter, randomized, placebo‐controlled, double‐blind, parallel‐group study in patients with GERD who experienced persistent symptoms while taking a stable dose of PPIs (ClinicalTrials.gov identifier: NCT01370863). Patients were randomized to either revexepride (0.5 mg, three times daily) or matching placebo for 4 weeks. Reflux events and associated characteristics were assessed by pH/impedance monitoring and disease symptoms were assessed using electronic diaries and questionnaires. Key Results In total, 67 patients were enrolled in the study. There were no significant differences between study arms in the number, the mean proximal extent or the bolus clearance times of liquid‐containing reflux events. Changes from baseline in the number of heartburn, regurgitation, and other symptom events were minimal for each treatment group and no clear trends were observed. Conclusions & Inferences No clear differences were seen in reflux parameters between the placebo and revexepride groups.